Episomal and integrated copies of Epstein-Barr virus coexist in Burkitt lymphoma cell lines. - Delecluse, H J (1993)
The Epstein-Barr virus genome is present in more than 95% of the African cases of Burkitt lymphoma. In this tumor, the viral genome is usually maintained in multiple episomal copies. Viral integration has been described only for Namalwa, a cell line lacking episomes. In this study, we have addressed the question of whether integrated and episomal copies can coexist in Burkitt lymphoma cells. Gel electrophoresis was used to demonstrate the presence of episomal as well as free linear DNA in three Burkitt lymphoma cell lines. The numbers of episomal copies per cell were estimated to be 5 to 10 in BL36 and BL137 cells and below 1 in BL60 cells, indicating that BL60 does not represent a homogeneous cell population. Fluorescence in situ hybridization was combined with chromosomal banding to study the association of the viral DNA with metaphase chromosomes. A symmetrical pattern of signals at both chromatids located at the same chromosomal sites in many if not all metaphases was taken as evidence for viral integration. In each of the three cell lines, one site of integration was identified: at chromosome 11p15 in BL36 cells, at chromosome 1p34 in BL137 cells, and at the site of a reciprocal t(11;19) translocation in BL60 cells. Integrated, episomal and linear copies of Epstein-Barr virus DNA thus coexist in Burkitt lymphoma cells. The biological significance of viral integration in Burkitt lymphoma cells remains to be elucidated.